Influence of Some Personal and Family Variables on Social Responsibility Among Primary Education Students - Martín-Antón, Luis J.; Carbonero, Miguel A.; Valdivieso, Juan A.; Monsalvo, Eugenio (Frontiers in Psychology, 2020)
One of the purposes of education is to help pupils develop a responsible attitude, which is understood to be the capacity to vouch for their actions appropriately and in a way that fits social norms. Training of this type should be intentional, planned and personalised, which will depend on how developed the individual's social responsibility is. This in turn is influenced by personal and family variables. This article provides an analysis of the interaction of some of those variables with the development of social responsibility in Primary Education pupils as the basis for the design of programmes to promote personal and social responsibility tailored to the features of the pupils. To do this, the Social Responsibility Attitudes Scale was applied to 502 pupils taking grades two (eight years old), four (ten years old) and six (twelve years old) of primary education. This scale measures the following factors: (a) obedient in family settings, (b) polite and accepting their mistakes, (c) trust in their parents, (d) responsibility in school setting, (e) friendly and willing to help, and (f) careful of the environment. By carrying out a multivariate analysis with the school grade, gender, family type (single, two-parent) and position among siblings (first-born, only child or not first-born), it was concluded that attitudes related to prosociality start to be differentiated from grade four of Primary Education. It is in grade six that children become aware of their responsibility and this is greater among those from two-parent families. However, no significant differences were found in the level of social responsibility with regard to gender or position among siblings.